Yield Criterion Accounting for the Third Invariant of Stress Tensor Deviator. Part I. Proposition of the Yield Criterion Based on the Concept of Influence Functions - NOWAK, M.; OSTROWSKA-MACIEJEWSKA, J.; PĘCHERSKI, R. B.; SZEPTYŃSKI, P. (Engineering Transactions, 2014)
A proposition of an energy-based hypothesis of material effort for isotropic materials exhibiting strength-differential (SD) effect, pressure-sensitivity and Lode angle dependence is discussed. It is a special case of a general hypothesis proposed by the authors in [11] for anisotropic bodies, based on Burzyński’s concept of influence functions [2] and Rychlewski’s concept of elastic energy decomposition [16]. General condition of the convexity of the yield surface is introduced, and its derivation is given in the second part of the paper. Limit condition is specified for Inconel 718 alloy, referring to the experimental results published by Iyer and Lissenden.